O lugar dos dados na análise da paisagem: o espaço rural goiano sob diferentes olhares, 1985-2017 - Lopes, Vanessa Cristina (2019)
The anthropic impact activities on land cover has reached an unprecedented extent significantly affecting major land biomes. Given these changes and the consequent environmental, social and economic impacts resulting from them, it is evident the impossibility of sustainable territorial management aimed meeting socioeconomic and environmental needs without the proper understanding of the landuse dynamics. Studies involving this theme are increasingly complex and cover various spatial and temporal scales. And, in order for these to be properly supported, data must be available to based them. A traditional source of land use and land cover data is census data and statistical inventories. Alternatively, remote sensing is a source of data production as well as a tool for landscape analysis, planning and management. The data produced by these different methodologies present peculiar aspects of applicability and quality standards. After all, different datasets build different landscapes leading us to the hypothesis that reality is not objective and that the landscape is constructed by available data and prevalent theoretical models. Given this problem, and in order to understand the impact of generated data by different methodologies in the studies and analyzes that appropriate them, three scenarios covering the dynamics of land use were analyzed. Scenarios 1 and 2 presented two narratives that reconstructed the Goiás land use dynamics, from 1985 to 2017, one through subjective data and the other through satellites data. Each of these constructions can be interpreted as a different point of view, that is, a way of looking at the same landscape, always underestimating or overestimating its elements, its composition, but never reaching the “real”, as demonstrated by comparative analysis presented in scenario 3. How does the reality evidenced by the data represent the real world? We can affirm that the landscape represented will always be a subjective function of the actors involved in this construction perception, by selecting the data to be used and defining the elements to be represented.